Factor Structure of a Spanish Translation of an Obesity-Specific Parent-Report Measure of Health-Related Quality of Life. (15th May 2018) - Borner, Kelsey B; Mitchell, Tarrah B; Gray, Jane S; Davis, Ann M; Pont, Stephen J; Sweeney, Brooke R; Hampl, Sarah; Dreyer Gillette, Meredith L
Abstract: Objective: Latino youth are disproportionately affected by pediatric obesity and consequently experience impaired health-related quality of life (HRQOL). Although many caregivers of Latino youth do not speak English fluently, no validated Spanish translations of obesity-specific HRQOL measures exist for this population. Therefore, non-English-speaking Latino parents have typically been excluded from analyses related to HRQOL. This study assesses the factor structure of a Spanish translation of a parent-report measure of obesity-specific HRQOL, Sizing Them Up, in a treatment-seeking sample of children with obesity. Methods: Structural equation modeling was used to assess the factor structure of the 6-subscale, 22-item Sizing Them Up measure in 154 parents of treatment-seeking Latino youth (5–18 years of age). Analyses exploring internal consistency and convergent validity were also conducted. Results: Acceptable measurement fit was achieved for the six-factor solution. However, the higher-order model assessing Total HRQOL did not reach acceptable levels, as results found that the Positive Social Attributes (PSA) subscale was not representative of Total HRQOL; internal consistency and convergent validity results also supported this finding. Conclusions: The current study provides support for the utility of a modified version of Sizing Them Up, excluding the PSA Scale, as a parent-report measure of obesity-specific HRQOL in treatment-seeking Latino youth with obesity.